Estudio correlacional entre el actual crecimiento demográfico y las perspectivas de desarrollo social en los países europeos - Jordán Totoy, Andrea Karen (My University, 2019)
The purpose of the investigation relies on the analysis among the correlation between social development and the demographic growth categories. Focusing on the creation of strategies that may be helpful to get to a possible solution around this problem that has to do with the old world. The main objective is to study different demographic growth categories and social development; parting from the compilation and analysis of theoretical information related to the problem as an analysis object; in perspective the construction of an interventional proposal. The investigation acquires theoretical fundamentals sustained within the bibliographical references among scientific papers generalized on indexed magazines. The investigation also presents arguments regarding epistemological arguments with the rational-inductive paradigm obtained through the recompilation of bibliographical data. Throughout the study it was evidenced that the migration waves play an important role regarding the European demographic development since the migration levels have multiplied because of the middle east conflicts. European governments, where the countries used to show low rates of population growth, are now progressively being immerse on social and economic conflicts focusing on how to attend the new social needs of immigrants and to also raise the living conditions of this community that are now considered deplorable, it is the change from a small, nuclear European family to the development of big and extensive families.
El propósito de la investigación reside del análisis de la correlación que existe entre las categorías de crecimiento demográfico y desarrollo social, enfocado en la elaboración de estrategias que puedan ser de gran aporte llegar a una posible solución en torno a este problema que suscita en el viejo mundo. El objetivo general se enmarca en estudiar las categorías de crecimiento demográfico y desarrollo social, a partir de la compilación y análisis de información teórica en correlación al problema objeto de estudio, en perspectiva de construcción de una propuesta interventiva. La investigación adquiere fundamentos teóricos sustentados en referencia bibliográfica de artículos científicos generalizados en revistas indexadas, asimismo adquiere argumentos en el referente epistemológico en el paradigma racional-inductivo obtenidos mediante la recopilación de datos bibliográficos. En el estudio realizado se evidenció que las oleadas migratorias juegan un papel importante en cuanto al desarrollo demográfico de Europa ya que esta se ha multiplicado en razón de los conflictos ocasionados en medio oriente. Los gobiernos europeos, en cuyos países se evidenciaban bajos niveles de crecimiento poblacional, progresivamente se han visto inmersos en un conflicto social y económico de cómo atender las nuevas demandas sociales de los inmigrantes y mejorar sus condiciones de vida deplorables.
Keywords: DESARROLLO; SOCIAL; CRECIMIENTO; MIGRANTE